Risk factors in age-related macular degeneration and glaucoma – own observations - Wierzbowska, Joanna; Figurska, Małgorzata; Stankiewicz, Andrzej; Sierdziński, Janusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To assess the differences between the prevalence of risk factors in patients with age- related macular degeneration (AMD), with glaucoma and with both diseases. Material and methods: The study included 255 patients, 156 F/99 M, in age 30 to 92 years, mean age 70.9 years. They were divided into 3 groups: AMD Group (83 patients, 46 F/37 M, mean age 71.5), Glaucoma Group (34 patients, 17 F/17 M, mean age 67.1) and AMD + Glaucoma Group (138 patients, 93 F/ 45 M, mean age 70.9). In all groups age, sex, family history of AMD and glaucoma, hypertension, hypotension, hypercholesterolemia, diabetes, coronary heart disease, vasospasm (cold hands), migraine, heart failure and stroke in anamnesis, smoking, type of diet (high or low fat intake, high or low vitamin intake), UV exposition, cataract surgery in anamnesis, bright-coloured iris, disc hemorrhages and peripapillary atrophy were determined, and compared between them. T-student test, ANOVA, Bonferoni, Kruskall-Wallis and chi-square tests and logistic analysis (likelihood ratio chi-square) were used for statistical analysis. Results: Family history of glaucoma were higher in the Glaucoma Group (odds ratio OR 9.0 p=0.004) than in the AMD Group (odds ratio OR 9.0 p=0.004) and than in the AMD + Glaucoma Group (OR 3.01 p=0.001). Disc hemorrhages were higher in the Glaucoma Group (OR 13.0 p=0,020) than in the AMD Group (OR 13.0 p=0.020). High fat intake in diet were lower in the Glaucoma Group as compared to the AMD Group (OR 0.5 p=0,03). Cholesterol high level and UV exposition were lower in the Glaucoma Group than in the AMD + Glaucoma Group (OR 0.278 p=0,020 and OR 0.23 p=0,040 respectively). Coronary heart disease and peripapillary atrophy were lower in the AMD Group as compared to the AMD + Glaucoma Group (OR 0.43 p=0.004 and OR 0.5 p= 0.040). Conclusions: The study has found that high fat intake in diet was higher in the patients with AMD and family history of glaucoma, and disc hemorrhages were higher in the patients with glaucoma. The following risk factors: high level of cholesterol, UV exposition, coronary heart disease and peripapillary atrophy, were higher in the patients with co-existing both diseases.